HOW PSYCHOLOGICAL ATTITUDES INFLUENCE A PERSON’S LIFE - Babayeva Nazira Asatullayevna (Web of Journals Publishing, 2024)
Psychological attitudes accompany us everywhere. Psychological attitudes are called a behavioral program that is embedded in a person’s subconscious. A person does not realize this fact or traces the trend after committing actions. Attitudes are formed depending on what we see most often. Everyone has settings. And this does not depend on age, gender, religion. Installation steps. I am good and you are good. I'm good and you're bad. I'm bad and you're good. I'm bad and you're bad.
Keywords: Installation steps. I am good and you are good. I'm good and you're bad. I'm bad and you're good. I'm bad and you're bad.